2013
DOI: 10.3109/0284186x.2012.744877
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported work ability in long-term breast cancer survivors. A population-based questionnaire study in Denmark

Abstract: Background . Although up to 80% of women can return to work after treatment for breast cancer, maintaining an affi liation to the labour market may be a challenge, as shown by the fact that the risks for unemployment and early retirement are increased in the years after treatment of cancer. It is important to understand the work problems experienced by cancer survivors, including their ability to work. The aim of this study was to determine whether the ability of long-term breast cancer survivors to work was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
93
3
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 26 publications
7
93
3
2
Order By: Relevance
“…It is obvious that this kind of support at the end is advantageous for both the employer and the employee. The importance of workplace support has been demonstrated in several studies [14,[15][16][17][18][19][20]33], but the current study might clarify the background to these findings.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…It is obvious that this kind of support at the end is advantageous for both the employer and the employee. The importance of workplace support has been demonstrated in several studies [14,[15][16][17][18][19][20]33], but the current study might clarify the background to these findings.…”
Section: Discussioncontrasting
confidence: 48%
“…For women who had survived breast cancer, poorer work ability than cancer-free controls was found. This poorer ability was strongly associated with little support at work [33].…”
Section: Discussionmentioning
confidence: 99%
“…A lower educational level is suggested to be a risk factor for decreased RTW in workers with prostate cancer . In some studies, poor economic status and low household income are considered barriers for RTW among breast cancer survivors . Ahn et al demonstrated that marriage was a negative predictor of employment and that married breast cancer survivors were less likely to RTW .…”
Section: Discussionmentioning
confidence: 99%
“…37 In some studies, poor economic status and low household income are considered barriers for RTW among breast cancer survivors. 38 Ahn et al demonstrated that marriage was a negative predictor of employment and that married breast cancer survivors were less likely to RTW. 39 In a previous study of patients with HNC, anxiety was indicated as a barrier to RTW after treatment for HNC survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Bradley et al (2005)[8] reported that African American women were 12 percentage points less likely to be employed than white women six months after diagnosis, but by 12 months following diagnosis, racial differences were no longer statistically significant [8]. Demographic characteristics such as age [9, 10] and low education [11-13], chemotherapy [10, 14-15] and radiation [14], physically demanding jobs and availability of sick leave [11, 16] work place discrimination, and accommodation influence return to work [17-19]. If African American women are diagnosed at later stages, they may require lengthy and toxic chemotherapy regimens, which would prevent them from returning to work relative to women diagnosed with earlier stage disease.…”
Section: Introductionmentioning
confidence: 99%